Czech journalists in the 21st century: who are they? - Nĕmcová Tejkalová, Alice; Láb, Filip (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
Who are Czech journalists and what do they do? Based on data from 291 interviews with Czech journalists working in the news media at various levels between 2012 and 2014, for the Worlds of Journalism Study (www.worldsofjournalism.org), the paper introduces for the first time an overview of the most important results of the Czech part of the study. We present an analysis of the data on journalists’ working conditions, the most and least important perceived influences on their work, as well as their level of trust in various institutions, recent significant changes perceived in their profession and the professional roles they prefer. The basic demographic data of our sample is also given. The survey was done in two phases, between which significant media ownership changes took place, making the results highly up-to-date. We conclude that the position of journalists is changing. Journalists are required to write more stories than before, yet have less time to research them. Although they assert the importance of journalistic ethics, they have also perceived that ethical standards have somewhat weakened recently. Nevertheless, they express a high level of autonomy and freedom in their work.